Assessment of static performance of LKAB´s welded mesh : Laboratory testing and analysis - Eriksson, Fredrik (Luleå tekniska universitet, Institutionen för samhällsbyggnad och naturresurser, 2020)
Surface support is an areal support, which is installed on rock excavation surface to prevent bulking of rock mass and retain loose rock fragments. Welded wire mesh is one type of surface support. Literature study indicates that there is a wide range of testing methods on mesh. Different setups regarding mesh configuration, installation, and load applying system are used to evaluate its load-bearing, deformation, and energy absorption capacities. Loads are applied in different ways to simulate both static and dynamic loading conditions. However, there is not any standardized testing method. Common configuration of a welded mesh sheet in LKAB´s underground mines has the dimension of 2.3 m × 2.5 m and is made of 5.5 mm (in diameter) wires welded with a square grid pattern of 75 mm × 75 mm spacing. It is installed with a square bolt pattern with a bolt spacing of 1.0 m × 1.0 m particularly in seismically active areas. Comprehensive field damage investigations at LKAB’s Kiirunavaara mine have shown localized failure of mesh, i.e., the mesh was cut or torn by rock blocks as a result of a seismic event. This is especially common along the mesh overlap where mesh sheets are joined together. However, the performance of welded mesh used at the LKAB’s mines and its performance along mesh overlap is not well understood. Laboratory tests of LKAB´s welded wire mesh were conducted at the Mining and Civil Engineering Lab at Luleå University of Technology. A test frame was built to test the mesh under static conditions after literature review. Mesh sheets with reduced dimension of 1.2 m x 1.2 m were mounted at the corner by four bolts on the frame and tested with different loading conditions in test series AA. In test series AB/AD, two mesh sheets with overlap were tested and the load was applied at the overlap between two bolts. For the base case in series AA, a rupture load of 41.4 kN was registered at a displacement of 0.44 m using the loading plate with the size of 0.07 m2 when the load was applied at the center of the ...